Expertise and Independence on Governing Boards: Evidence from School Districts - Ying Shi; John D. Singleton (Institute of Labor Economics (IZA), 2019)
In this paper, we study the roles of expertise and independence on governing boards in the context of education. In particular, we examine the causal influence of professional educators elected to local school boards on education production. Educators may bring valuable human capital to school district leadership, thereby improving student learning. Alternatively, the independence of educators may be distorted by interest groups. The key empirical challenge is that school board composition is endogenously determined through the electoral process. To overcome this, we develop and implement a novel research design that exploits California's randomized assignment of the order that candidates appear on election ballots. The insight of our empirical strategy is that ballot order effects generate quasi-random variation in the elected school board's composition. This approach is made possible by a unique dataset that combines election information about California school board candidates with district-level data on education inputs and outcomes. The results reveal that educators on the school board causally increase teacher salaries and reduce district enrollment in charter schools relative to other board members. We do not find accompanying effects on student test scores. We interpret these findings as consistent with educators on school boards shifting bargaining in favor of teachers' unions.
Keywords: I20; H75; J24; 330; school boards; education; ballot order effects; education production; expertise; independence